Master of disguise - Baker, Eugene H.; Axeman, Lois. (Elgin, Ill. : Child's World ; Chicago, Ill. : distributed by Childrens Press, 1980)
Discusses the importance of observation and the uses of disguises in detective work.
Keywords: Private investigators; Impersonation; Detectives; Impersonation